VILLAGE FUND MANAGEMENT BASED ON PERMENDAGRI 20/2018 - Rina Maulina; Riyan Arfansyah; Sari Maulida Vonna; Linda Rahmazaniati; Ika Rahmadani (Jurnal Aplikasi Akuntansi, 2023)
This research aims to determine the process of preparing the RPJMG, RKPG, and Gampong Revenue and Expenditure Budget (APBG) in Gampong Simpang Dua based on Permendagri number 20 of 2018. The interview method is used for this research, where questions are asked orally. Village officials who are responsible for managing village funds have been selected as respondents. Gampong Simpang Dua, Nagan Raya Regency, is where this research takes place. In order to use the interactivity of data analysis techniques such as APBDesa, RKPDesa, DPA, DPPA, DGKPL, and accountability reports, this research is conducted using a qualitative descriptive research methodology. The results of this analysis confirm that the village's financial management takes place in accordance with Minister for Home Affairs Regulation No. 20 of 2018 based on planning, implementation, administration, reporting, and accountability processes. As seen from the preparation of the Gampong RPJM for 6 years, it is reported through the Village Financial System (SISKUEDES) application, where this report is input when the Gampong treasurer inputs the Gampong cash receipts and expenditures